Adjustment problems and needs of educable mentally retarded children and how these problems and needs can be properly met in the school - Nagrampa, Josefina F. 1932- (1967)
The purpose of the study was to determine the adjustment problems and needs of educable mentally retarded children and how these problems and needs can be properly met in the school in order to effect adequate personal and social adjustment. A program of research reading of pertinent materials relative to the study was undertaken. The study showed that the adjustment problems of educable mentally retarded children include withdrawing, shyness, unsociableness, bullying, fighting, frustrations, aggressions, isolation, truancy, cheating, no interest in school work and sometimes displaying temper tantrus and others.